(untitled) (Journal of Partial Differential Equations, 1995)
We consider a free boundary problem in a parabolic partial differential equation with multiple interfacial curves which is reduced to a reaction-diffusion equation. The forcing term of this problem is not continuously differentiable and thus we use Green's function to make a regular one. The existence, uniqueness and dependence. on initial conditions will be shown in this paper.